Conformal and Flexible Antennas in Ultra-High Frequencies: Prospects and Challenges for Partial Discharge Diagnostics - M. A. Taher; Mohamadariff Othman; Hazlee Azil Illias; Tarik Abdul Latef; Tengku Faiz Tengku Mohmed Noor Izam; S. M. Kayser Azam; Muhammad Ubaid Ullah; Mohamed Alkhatib; Mousa I. Hussein (IEEE Access)
With the exponential increase in smart device usage across various domains, flexible and conformal antenna technologies have emerged as transformative solutions, enabling wireless systems in numerous smart applications. However, selecting a suitable flexible and conformal substrate remains challenging because of the intricate characteristics and performance considerations of each material. Additionally, most applications of these substrates are confined to specific areas, such as body-worn devices, biomedical uses, and health services. In contrast, the use of ultra-high frequency (UHF, 0.3–3 GHz) antennas is largely concentrated in radio frequency identification (RFID) and telecommunications, with limited exploration in other areas. Recently, UHF antennas have gained attention for unconventional applications, including high-voltage (HV) defect detection, particularly partial discharge (PD) diagnosis. However, practical challenges arise due to the rigidity of commercial substrate materials. This paper provides a comprehensive survey on flexible and conformal UHF antennas’ applicability for PD diagnostics, a field that remains underexplored. We systematically assess the electrical, mechanical, and thermal properties of various flexible and conformal substrates relevant to UHF antenna development. In this investigation, we thoroughly analyse five substrate materials, namely polyimide (PI), polydimethylsiloxane (PDMS), Rogers laminates, polytetrafluoroethylene (PTFE), and polyethylene terephthalate (PET), and several types of UHF antennas including planar monopole, spiral antenna, Hilbert antenna, biconical antenna, and so on. The synthesis of this research delivers a complete roadmap, addressing existing limitations and proposing future directions for PD diagnosis by conformal and flexible antennas.